Gill Junction Injury and Microbial Disorders Induced by Microcystin-Leucine Arginine in Lithobates catesbeianus Tadpoles - Huiling Jiang; Jun He; Hui Wang; Lingling Zheng; Xiaoran Wang; Huijuan Zhang; Hailong Wu; Yilin Shu (Toxins, 2022)
Microcystin-LR (MC-LR) is widely present in waters around the world, but its potential toxic effects and mechanisms on amphibian gills remain unknown. In the present study, tadpoles (Lithobates catesbeianus) were exposed to environmentally realistic concentrations of 0.5, 2 μg/L MC-LR, and 0 μg/L MC-LR (Control) for 30 days with the objective to unveil the impairment of gill health. The lysozyme was downregulated, while pattern recognition receptors and complement and adaptive immune processes were upregulated and the ability of gill supernatant to inhibit pathogenic bacteria decreased in the 0.5 and 2 μg/L MC-LR groups. The transcriptions of epithelial barrier components (e.g., CLDN1) were significantly decreased in MC-LR-exposed gills, while the gill content of lipopolysaccharide (LPS) endotoxins and the transcriptions of downstream responsive genes (e.g., TLR4 and NF-κB) were concurrently increased. In addition, the number of eosinophils and the expression of pro-inflammatory cytokines (e.g., IL-1β and TNF-α) were increased. These results imply that exposure of tadpoles to low environmentally concentrations of MC-LR leads to inflammation, increased permeability, and a reduced ability to inhibit pathogenic bacteria. The epithelial cells of inner gill filaments increased and transcriptions of hypoxic stress genes (e.g., HIF-1α, FLT1, and SERPINE1) were upregulated within the exposed group. As a consequence, exposure to MC-LR may lead to hypoxic stress. MC-LR exposure also drove gill microbiota to a dysbiosis. The relative abundance of Elizabethkingia was positively correlated with content of LPS and transcriptions of NF-κB and TNF-α. Overall, this study presents the first evidence about the pronounced impacts of MC-LR exposure on gills of amphibians, highlighting the susceptibility of early developing tadpoles to the environmental risks of MC-LR.